Modified Arthroscopic McLaughlin Procedure in the Treatment of Posterior Glenohumeral Instability- Technical Note - Tiago Pinheiro Torres; Sara Lima; Manuel Gutierre (Revista Brasileira de Ortopedia)
Abstract The diagnosis of and the treatment for traumatic posterior shoulder dislocation are challenging. Some series describe that between 60 and 80% of these lesions are not diagnosed during the first visit to the emergency room. As such, dislocations are frequently found after several days or even weeks, adding complexity to their treatment. Posterior dislocations are usually accompanied by a print fracture on the anterior surface of the humeral head, known as reverse Hill-Sachs injury. This bone defect can “engage” into the posterior glenoid ridge, leading to recurrent instability and progressive joint destruction. The authors describe a modified arthroscopic McLaughlin procedure, which allows filling the bone defect with the upper third of the subscapular tendon, avoiding recurrence of the posterior instability. Next, a posterior Bankart lesion repair is performed along with a tenodesis of the long portion of the bicipital tendon. This technique, in addition of repairing the posterior chondrolabral lesion, creates a remplissage effect, making the repair stronger and representing an optimal procedure for the definitive treatment of recurrent posterior luxation. It is an entirely arthroscopic procedure, avoiding the disadvantages of an open procedure.